Outcomes of the Surgical Management of Atrial Isomerism and Functional Single Ventricle: A Single-Centered Cohort From China - Zou, Ming-Hui; Cao, Fan; Ma, Li; Chen, Wei-Dan; Li, Wen-Lei; Li, Jia; Chen, Xin-Xin (Frontiers in Cardiovascular Medicine, 2021)
Objectives: The management of atrial Isomerism with complex congenital heart disease remains challenging. Experience has been largely obtained in the advanced countries. The clinical diversity is greater in China. We evaluated the early- and medium-term outcomes of surgical treatment of these patients. Methods: We reviewed 86 patients of atrial Isomerism with complex congenital heart disease undergoing varied surgeries in our center in 2008–2020. Cox regression models were used to analyze the risk factors for mortality. Results: There were 75 cases of right and 11 of left atrial isomerism. Eighty-three (96.5%) patients underwent single ventricle staged palliation approach, with 10 early and 7 late deaths. The overall 1-, 5-, and 10-year survival rates were 84.7%, 79.3%, and 79.3%, respectively. Thirty-six (43.4%) patients completed Fontan procedure with median age of 48 months, and the freedom from death or Fontan failure at 1-, 5- and 8-year were 94.4%, 87.4% and 80.7%, respectively. Concomitant total anomalous pulmonary venous connection (HR: 5.15 (1.95–12.94), P=0.008), more than moderate atrioventricular valve regurgitation (HR: 4.82 (2.42–6.79), P=0.003), and the need for first-stage palliative surgery (HR: 4.58 (1.64–10.76), P=0.015) were independent risk factors for mortality. Conclusions: Despite of even greater clinical diversity, the surgical outcomes of atrial Isomerism with complex congenital heart disease are improving in China. The early and intermediate outcomes are comparable to many of previous reports. Concomitant total anomalous pulmonary venous connection, moderate or severe atrioventricular valve regurgitation, and the need for a first-stage palliative surgery are still independent risk factors for mortality.